2018
DOI: 10.1016/j.clnu.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of body composition in anorexia nervosa: Results from a retrospective study

Abstract: This study shows that the selected predictive BIA equations considered exhibit an insufficient accuracy at the population and the individual level. Predictive formulas based on body weight plus BIA parameters such as RI and ZI offer a rather accurate prediction of FFM (with high R squared).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
(21 reference statements)
1
15
0
Order By: Relevance
“…However, DXA is not routinely used in clinical practice, contrary to BIA [ 13 , 34 ] whereas no widely disease-specific equation has been accepted for the estimation of body composition in these AN patients. Recently, Marra et al assessed the accuracy of selected BIA equations [ 35 , 36 ] for FFM estimation in 82 female patients with AN and reported that all predictive equations underestimated FFM, while the percentage of accurate predictions varied from 12.2% to 35.4% [ 25 ]. Interestingly, in this recent study, predictive formulas based on body weight and BIA parameters such as RI (resistance index) and ZI100 (impedance index at 100 kHz) offered a rather accurate prediction of FFM (with high resistance squared) than that observed with anthropometric characteristics only.…”
Section: Discussionmentioning
confidence: 99%
“…However, DXA is not routinely used in clinical practice, contrary to BIA [ 13 , 34 ] whereas no widely disease-specific equation has been accepted for the estimation of body composition in these AN patients. Recently, Marra et al assessed the accuracy of selected BIA equations [ 35 , 36 ] for FFM estimation in 82 female patients with AN and reported that all predictive equations underestimated FFM, while the percentage of accurate predictions varied from 12.2% to 35.4% [ 25 ]. Interestingly, in this recent study, predictive formulas based on body weight and BIA parameters such as RI (resistance index) and ZI100 (impedance index at 100 kHz) offered a rather accurate prediction of FFM (with high resistance squared) than that observed with anthropometric characteristics only.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BIA may not be the ideal BC assessment tool for severe grade AN 40 , but several studies 1,41,42 found it to be appropriate in mild-to-AN clinics.…”
Section: Limitationsmentioning
confidence: 99%
“…Finally, comparison of BC assessment by DXA and BIA in obese patients has been poorly documented. A few studies have shown good concordance between the two methods [ 39 , 40 ] while many others have not [ 15 , 17 , 41 , 42 , 43 , 44 , 45 , 46 ]. These conflicting results may probably be due to some limiting factors including the use of different BIA devices with different manufacturer equations, a small population size, and the differences in age, ethnicity and body weights in the sample studied.…”
Section: Strengths and Limitationsmentioning
confidence: 99%